Vascular dementia has the highest hospitalisation rate in China: a nationwide hospital information system study. Issue 1 (6th September 2022) - Wang, Yue; Li, Shiping; Zhou, Qi; Wang, Yongjun; Shi, Jiong
Abstract : Background: Although vascular dementia (VaD) is not uncommon in the hospital, most studies on VaD are community based. This study on VaD is the first to use a national hospital information system (HIS) in China. Methods: This study was a hospital population-based cohort study, and data were acquired from the Hospital Quality Monitoring System, a Chinese national database that covers 1531 tertiary hospitals in China. The medical records in the HIS included demographic information, diagnoses, procedures, expenses, etc. VaD was diagnosed by hospital attending physicians and identified by the International Classification of Diseases (ICD) 10 code (F01.0-F01.9). Results: 1259 (82.23%) tertiary hospitals were included in this study, and 274 230 hospitalisation records of 123 700 VaD patients from 2016 to 2018 were identified for analysis. VaD (51.27%) was the most common type of dementia in hospitalised patients. The age-adjusted and sex-adjusted hospital incidence of VaD was estimated to be 2.97 per 100 000 person-years (95% CI 2.92 to 3.02). The mean age of VaD patients admitted to hospitals was 74.13±10.88, with more male (61.0%) patients. The main comorbidities were hypertension (67.2%), heart disease (63.6%) and cerebral infarction (55.5%). The mortality rate of VaD in hospital was 28.91‰ (95% CI 28.0 to 29.9) between 2016 and 2018. The top 1 cause of death due to VaD was pneumonia and other respiratory disorders. Conclusions: VaD is the most common form of dementia in hospitalised patients. It casts huge burdens on affected patients and their caregivers. Vascular risk factors are prevalent in VaD patients. Reducing these factors is essential to improve patient care. The leading causes of death by VaD are pneumonia and other respiratory disorders. Hospital care and the management of respiratory illness are critical for VaD care in the hospital.